Wirtschaftspolitik für die Eurozone - Paul Atkinson; Wolfgang Michalski; Leif Pagrotsky; Robert Raymond; Kumiharu Shigehara (Wirtschaftsdienst, 2014)
Die Eurokrise hat ihren Ursprung nicht nur in einer Staatsschuldenkrise. Sie wurde ebenfalls durch eine Zahlungsbilanzkrise verursacht. Ein breit gefächerter Ansatz in der Wirtschaftspolitik ist daher erforderlich, um die Eurozone auf einen nachhaltig stabilen und dynamischen Wachstumspfad zurückzubringen. – – A multi-faceted approach is required for the euro area to restore sustainable growth and prevent a vicious circle of public- and private-sector deleveraging leading to weaker economic activity which in turn results in a further deterioration in banks' asset quality. While avoiding discretionary fiscal expansion, creditor countries should work together with debtor countries to accelerate micro-economic reforms in product, services and labor markets to achieve greater macro-economic convergence in the euro area. This, with together the restoration of the health and resilience of the banking sector, is the key to the area's viability. The ECB's policy to avoid any deflationary bias while stabilizing inflation at or around 2 per cent for the euro-area as a whole should be another component of such an approach.
Keywords: E44; E58; E65; F33; F34; G1; 330